Peace Studies at Bradford University – Reflections on Fifty Years - Rogers, Paul (Quaker studies, 2023)
2023 marked the 50th anniversary of Peace Studies - a discipline which has been closely connected with the Quaker community - at Bradford. Peace Studies as an academic centre of teaching and research at Bradford University was set up in 1973, starting its first postgraduate course in 1974 and welcoming its first undergraduate students the following year. It would not have been established without the determination of a group of Quakers to see such a centre in a UK university, and this Research Note looks primarily at the first 25 years and how the department came about and survived the many internal and external challenges. It also includes some personal reflections, as I joined the department 45 years ago and have retained a close connection through to the present.